Evaluación de procesos administrativos para la gestión empresarial de empresas gastronómicas del destino Portoviejo - Solórzano Vera, Ronald Mariano (2021)
This research is descriptive in nature, with the purpose of evaluating the administrative processes of second and third category gastronomic companies of the Portoviejo canton to improve their business management. 3 specific objectives were defined, developed in 3 methodical phases based on the Castaño (2013) methodology. In phase I, the study area was diagnosed through bibliographic and documentary review, as well as the application of the SWOT strategic analysis matrix; Later, in phase II, the administrative processes of gastronomic companies were evaluated through a system of indicators, in which interviews were used, and in phase III, through the flowchart technique, a process diagram was designed from which an administrative management system was defined. The main results are based on the evaluation of the administrative processes of gastronomic companies, where it was determined that 15% of the administrative processes stipulated in the management indicators are not applied. Based on this, an administrative management system was designed that focuses on customer needs, key actors and satisfaction based on administrative functions: planning, organization, direction and control; In addition, 5 objectives were drawn up aligned with 10 strategies that led to the development of an action plan that includes 7 programs with their respective actions, determining those responsible, resources, time and control measures for their execution in the gastronomic companies of Portoviejo.